STATE OF AFFAIRS OF EDUCATION: THE PERSPECTIVE OF RETIRED TEACHERS - Ryan Fernando; Agung Pramana, Mantilie, Elawati, Rema Valencia, Alpida, Yola Pradita (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
This journal of Educational Psychology discusses the condition of education from the point of view of retired teachers. This study was conducted to determine the views and experiences of retired teachers on the current state of Education. The method used is a structured interview with 10 teachers who have retired. The results showed that retired teachers have a diverse view of the current state of Education. Some teachers feel that education today is better compared to the past, but most teachers feel that education today is in decline. Retired teachers also revealed some problems in education today, such as lack of quality teachers, lack of motivation of students, and lack of government attention to education. This study provides a clear picture of the views and experiences of retired teachers on the current state of education, so that it can be a reference for related parties to improve the quality of education in the future.